Antibiotic-resistant bacteria and resistance-genes in drinking water source in north Shoa zone, Amhara region, Ethiopia - Tsegahun Asfaw Abebe; Demissew Shenkute Gebreyes; Bizuneh Asfaw Abebe; Berhanu Yitayew (Frontiers Media S.A., 2024)
BackgroundThe growing number of antimicrobial-resistant bacteria in a range of environments poses a serious challenge to infectious disease prevention. Good water quality is critical to human health and has a direct impact on a country's socio-economic growth. Therefore, assessing the bacteriological quality of drinking water provides benchmark data and provides insight into the development of further protection and treatment measures.MethodsA cross-sectional study was conducted from February 1, 2022, to September 31, 2023, in the diarrhea hotspot areas of North Shewa Zone (Minjar-Shenkora and Mojana-Wedera districts). Water samples were collected from drinking water sources (hand-pumps, boreholes, wells, spring water and ponds) to assess the quality following WHO guidelines. The collected water samples were processed for bacterial isolation, antimicrobial susceptibility testing, and detection of antimicrobial resistance genes. Data were entered and analyzed using the Statistical Package for the Social Sciences (SPSS) version 25.ResultsA total of (49/138, 35.5%) bacteria were isolated from 138 drinking water samples, with a positive rate of (41/138, 29.7%). Among the isolates, (16/138, 11.6%) were Staphylococcus aureus while (33/138, 23.9%) were members of Enterobacteriaceae. Relatively high resistance rate among all isolates were observed for the most prescribed antibiotics in Ethiopia, including erythromycin, cotrimoxazole, doxycycline, ceftriaxone, gentamicin, and chloramphenicol. However, a low resistance was observed for early introduced antibiotics such as ciprofloxacin and recently introduced antibiotics such as cefotaxime, ceftazidime, imipenem, and meropenem. Among the 49 bacteria isolates, (32/49, 65.3%) were multidrug-resistant (MDR) pathogens while (12/49, 24.5%) were ESβL producers. Different ESβL genes were detected in most bacterial isolates. The predominant ESβL genes were blaCTX-M-gp8/25 (6/33, 18.2%), blaCTX-M-gp9 (5/33, 15.2%), and blaCTX-M-gp1 (5/33, 15.2%).ConclusionThe result of this study suggests that most water sources in the study area were contaminated by various bacterial species that are resistant to different antibiotics. Various ESβL resistance genes have also been detected. Therefore, regular sanitary inspection and bacteriological analysis should be mandatory to protect drinking water sources from contamination and the persistence of resistant bacteria.